The influence of Halal Label, Product Quality, and Price on Purchasing Decisions - Cut Tari Fadila; Talbani Farlian; Arroyyan Ramly (Journal of Finance and Islamic Banking, 2020)
This study aims to analyze the influence of halal label, product quality, and price on purchasing decisions with a case study at the Bread Boy Bakery & Cake Shop in Banda Aceh. This research is quantitative research. The sample used was 100 respondents using a purposive sampling technique. The results of data processing carried out using the SPSS 22 program through the multiple linear regression analysis methods shows that the independent variables are halal labels, product quality, and price simultaneously or simultaneously have a positive and significant effect on purchasing decisions. While partially, the halal label variable does not have a positive and significant effect on purchasing decisions. While the product quality variable partially influences the purchasing decisions. The price variable has a positive and significant effect on purchasing decisions.